Three-Dimensional Quantification of Facial Asymmetry in Children with Positional Cranial Deformity. Issue 6 (29th November 2021) - Naros, Andreas; Wolf, Jan A.; Krimmel, Michael; Kluba, Susanne
Abstract : Background: The extent of facial involvement in positional plagiocephaly is only little investigated so far. Investigation methods that take into account the challenging anatomical conditions and growth of infants' faces are desirable. In this study, the authors established a new three-dimensional photogrammetry quantification method evaluating pretherapeutic and posttherapeutic facial asymmetry in positional plagiocephaly. Furthermore, a facial asymmetry index was established and evaluated. Methods: Three-dimensional photographs of 100 children undergoing treatment with head orthoses were analyzed by constructing a standardized interindividual coordinate system. Defining landmarks, section planes, and point coordinates with a computer-aided design software, both sides of the faces were compared. Facial asymmetry was quantified by measuring differences between left and right sides and pretherapeutic and posttherapeutic changes in each patient. The facial asymmetry index was calculated by putting the absolute differences in relation with the coordinates of the nonaffected side. Results: Present results indicate that positional plagiocephaly results in a distinct facial asymmetry (range, −3.8 to 9.6 mm) in nearly all spatial directions and facial regions. Helmet therapy led to a significant reduction ( p < 0.05) of intraindividual facial asymmetry (median change in facial asymmetry index, −1.9 to 3.1 percent). However, no correlation of the Cranial Vault Asymmetry Index and facial asymmetry (Spearman rank correlation coefficient, ρ = –0.09 to 0.47) has been seen. According to these results, severe occipital deformation does not necessarily provoke distinct facial asymmetry. Conclusions: Present three-dimensional photogrammetry method allows the longitudinal quantification of facial involvement in positional plagiocephaly. Asymmetry has been determined in all facial regions. The facial asymmetry decreased through helmet therapy but was not eliminated completely.